Towards a cervical cancer-free future: women’s healthcare decision making and cervical cancer screening uptake in sub-Saharan Africa - Bright Opoku Ahinkorah; Abdul-Aziz Seidu; Richard Gyan Aboagye; Bernard Yeboah-Asiamah Asare; Joshua Okyere; Bupe Mwamba (BMJ Open)
Objective We investigated the association between women’s healthcare decision making and cervical cancer screening uptake in sub-Saharan Africa.Design Secondary data from the Demographic and Health Surveys of six countries in sub-Saharan Africa were used. We employed multilevel binary logistic regression modelling.Setting Sub-Saharan Africa.Participants Women aged 15–49 years in Benin (n=5282), Côte d’Ivoire (n=1925), Cameroon (n=7558), Kenya (n=6696), Namibia (n=1990) and Zimbabwe (n=5006).Primary outcome measures Cervical cancer screening uptake.Results The overall prevalence of cervical cancer screening across the six sub-Saharan African countries was 13.4%. Compared with women whose healthcare decisions were made solely by husbands/partners/someone else, the likelihood of cervical cancer screening uptake was significantly higher among women who took healthcare decisions in consultation with their husbands/partners (aOR=1.38; 95% CI 1.19 to 1.59), but highest among those who made healthcare decisions alone (aOR=1.66; 95% CI 1.44 to 1.91). Women aged between 40 and 45 years (aOR=5.18; 95% CI 3.15 to 8.52), those with higher education (aOR=2.13; 95% CI 1.57 to 2.88), those who had ever heard of cervical cancer (aOR=32.74; 95% CI 20.02 to 53.55), read newspaper or magazine at least once a week (aOR=2.11; 95% CI 1.83 to 2.44), listened to the radio at least once a week (aOR=1.35; 95% CI1.18 to 1.52) and those in households with richest wealth index (aOR=1.55; 95% CI 1.20 to 2.00) had significantly higher odds of screening for cervical cancer compared to their counterparts.Conclusion Women who are able to make autonomous healthcare decisions and those who practice shared decision making are more likely to uptake cervical cancer screening. Therefore, policy interventions should focus on empowering women to be able to take autonomous healthcare decisions or shared decision making while targeting subpopulations (ie, multiparous and rural-dwelling women, as well as those in other religious affiliations aside from Christianity) that are less likely to uptake cervical cancer screening. Also, the radio and print media could be leveraged in raising awareness about cervical cancer screening to accelerate cervical cancer screening uptake in sub-Saharan Africa.